2009
DOI: 10.4103/0973-1075.53510
|View full text |Cite
|
Sign up to set email alerts
|

Role of percutaneous nephrostomy in advanced cervical carcinoma with obstructive uropathy: A case series

Abstract: Aims and Objective:Over 70% of the cases present in advanced stages of the disease and are associated with poor prognosis and high mortality rates. In many of them, it is difficult to offer definitive treatment as they present in uremia due to associated obstructive uropathy. There are no clear-cut guidelines for performing percutaneous nephrostomy (PCN) in patients of advanced cervical cancer. The results are unpredictable in terms of benefits achieved in these cases. Thus, we evaluated our experiences with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 9 publications
(14 reference statements)
2
32
1
2
Order By: Relevance
“…This finding is consistent with previous study undergoing palliative urinary diversion for ureteric obstruction in patients having gynaecological malignancy along with symptomatic improvement over a period of 1-3 weeks post PCN [17][18][19]. These studies confirm that urinary diversion can cause rapid restoration of renal function and evasion of the complications of uraemia.…”
Section: Effectivenesssupporting
confidence: 82%
“…This finding is consistent with previous study undergoing palliative urinary diversion for ureteric obstruction in patients having gynaecological malignancy along with symptomatic improvement over a period of 1-3 weeks post PCN [17][18][19]. These studies confirm that urinary diversion can cause rapid restoration of renal function and evasion of the complications of uraemia.…”
Section: Effectivenesssupporting
confidence: 82%
“…This finding is consistent with previous study undergoing palliative urinary diversion for ureteric obstruction in patients having gynaecological malignancy along with symptomatic improvement over a period of 1-3weeks post PCN. [17][18][19] These studies confirm that urinary diversion can cause rapid restoration of renal function and evasion of the complications of uraemia. PCN also caused lower complication rates therefore, is superior to intraureteral stenting.…”
Section: Effectivenesssupporting
confidence: 58%
“…Mishra et al reported that the average 5-year survival of cervical cancer patients without urethral obstruction and normal kidney function was 47%, whereas if there is obstruction of the ureter the survival was 29%. 5 Kidney failure in cervical cancer is mostly (90%) caused by high location of the obstruction in the ureter due to compression of the tumor mass. Cervical cancer can spread to surrounding structures including a lower segment of the uterus, vagina, paracervical and parametrial spaces.…”
Section: Introductionmentioning
confidence: 99%